A functional mutation associated with piglet diarrhea partially by regulating the transcription of porcine STAT3 - Chen, Zhihua; Yao, Diwen; Guo, Dongchun; Sun, Yuan; Liu, Lu; Kou, Mingxing; Yang, Xiuqin; Di, Shengwei; Cai, Jiancheng; Wang, Xibiao; Niu, Buyue (Frontiers in Veterinary Science, 2022)
The present study aimed to search for functional mutations within porcine STAT3 and to provide causative genetic variants associated with piglet diarrhea. We confirmed that STAT3 expressed higher in the small intestine than in the spleen, stomach and large intestine of SPF piglets, respectively (p < 0.05). A deleterious non-synonymous single nucleotide polymorphism (nsSNP) c.1413 C>T in the coding region and three mutations SNP1: g.-870 G>A, SNP2: g.-584 A>C and a 6-bp indel in the promoter region that displayed significant differential transcriptional activities were identified. Association analyses showed that SNP1 was significantly associated with piglet diarrhea (p < 0.05). Further functional analysis revealed that E2F6 repressed the transcriptional efficiency of STAT3 in vitro, by binding the G allele of SNP1. The present study suggested that SNP1 was a piglet diarrhea-associated variant that directly affected binding with E2F6, leading to changes in STAT3 transcription which might contribute to piglet diarrhea susceptibility or resistance.